2015
DOI: 10.1091/mbc.e15-06-0358
|View full text |Cite
|
Sign up to set email alerts
|

Experimental testing of a new integrated model of the budding yeast Starttransition

Abstract: Mathematical modeling of the cell cycle has unveiled recurrent features and emergent behaviors of cellular networks. Constructing new mutants and performing experimental tests during development of a new model of the budding yeast cell cycle yields a more efficient modeling process and results in several testable hypotheses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 100 publications
8
27
0
Order By: Relevance
“…As expected, the cln1D strain exhibited a glycerol-specific large phenotype, whereas the cln2D strain exhibited a large phenotype on both glucose and glycerol medium ( Figure 5A). We observed only a subtle size increase for the mbp1D strain in glucose medium, in agreement with previous reports (Flick et al, 1998;Bean et al, 2005;Adames et al, 2015). In glycerol medium, mbp1D cells exhibited a large size phenotype when compared with the WT control (Figure 5A).…”
Section: Sbf and Mbf Concentrations Are Upregulated In Glycerol Mediumsupporting
confidence: 93%
“…As expected, the cln1D strain exhibited a glycerol-specific large phenotype, whereas the cln2D strain exhibited a large phenotype on both glucose and glycerol medium ( Figure 5A). We observed only a subtle size increase for the mbp1D strain in glucose medium, in agreement with previous reports (Flick et al, 1998;Bean et al, 2005;Adames et al, 2015). In glycerol medium, mbp1D cells exhibited a large size phenotype when compared with the WT control (Figure 5A).…”
Section: Sbf and Mbf Concentrations Are Upregulated In Glycerol Mediumsupporting
confidence: 93%
“…The Whi5-Nsr1-GFP chimera was present at a slightly lower concentration, 80-100nM ( Figure 6A), close to endogenous Nsr1 nuclear levels in nitrogenlimited media (60-80nM, see Figure 2C). This slight decrease in Whi5 abundance was unlikely to explain the small size of cells expressing Whi5-Nsr1-GFP since cell size is not strongly sensitive to WHI5 gene dosage (45). We confirmed that hemizygous WHI5/whi5 diploid cells were only marginally smaller than WT diploid cells ( Figure S5E) and WHI5 overexpression only causes a 20-30% increase in mode size ( Figure 3C), in agreement with previous results (45).…”
Section: Nsr1 Contributes To Bypass Whi5 Inhibition Of Sbfsupporting
confidence: 92%
“…First, because of the central roles played by SBF, MBF and Cln3 in the START transition of the budding yeast cell cycle, we addressed our new results suggesting a viable phenotype for swi4D cln3D double-mutant cells in opposition to previous reports that swi4D cln3D is a synthetic lethal strain 33 . To 'rescue' swi4D cln3D cells, we significantly increased the activation of MBF (Swi6:Mbp1) by Bck2 (the only activator of MBF in the absence of Cln3), while simultaneously increasing the inactivation of MBF by Clb2 and decreasing slightly the activation of MBF by Cln3, in order to keep the level of MBF activity similar to that of the previous model, thus minimizing the perturbations to all other mutants that were previously explained by the model.…”
Section: Comparing the Results Of Our Screen With Previously Reportedmentioning
confidence: 90%
“…Ideally, one should combine top-down and bottom-up data, but huge discrepancies of scale between these two data types present barriers to integrating and understanding the hypotheses derived from each approach 11-17 .To mitigate these problems, many researchers, including ourselves, have developed detailed mathematical models that integrate top-down and bottom-up approaches in order to describe the molecular mechanisms that underlie cell cycle regulation in budding yeast 4, 17-22 . The governing equations of the model are simulated on a computer, and the model (the 'wiring diagram' of molecular interactions) is adjusted until it generates dynamic behaviors that reflect the documented molecular changes and general network behaviors observed in cells (e.g., cell viability, timing of cell cycle events, cell size at birth, response to DNA damage or chromosome misalignment at mitosis) [23][24][25][26] . Often, the documented data is missing detailed molecular information, such as protein concentrations and rate constants of crucial reactions, but fitting the model (i.e., fine-tuning the parameter values) to extensive sets of phenotypic data usually introduces strong constraints on these unknown parameters 19, 27 .…”
mentioning
confidence: 99%